Unveiling fieldbus network technology through project-based learning - De Lucena, Samuel E. [UNESP]; Mogames, Omar [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Fieldbus communications networks are a fundamental part of modern industrial automation technique. This paperwork presents an application of project-based learning (PBL) paradigm to help electrical engineering students grasp the major concepts of fieldbus networks, while attending a one-term long, elective microcontroller course. © 2012 IEEE.
Keywords: automation; fieldbuses; Hands-on education; microcontrollers; networks; projec-based learning; Communications networks; Electrical engineering students; Field bus; Fieldbus networks; Hands-on educations; Industrial automation techniques; Project based learning; Automation; Microcontrollers; Networks (circuits); E-learning